LEARNING INDONESIAN LANGUAGE MAIN IDEAS MATERIAL USING STICKY NOTES TEACHING MEDIA - Ahmad Faisal, Muhammad Pauzan, Sri Wahyuni, Ahmad Faisal (jurnalalfa, 2024)
The aim of this research is to describe the learning outcomes of Indonesian language learning main idea material using teaching media sticky note. Qualitative descriptive research method with up to 30 students. The research location is the Madrasah Ibtidaiyah STAIN Madina teacher education study program. The results of the research description regarding learning Indonesian main idea material using teaching media sticy note are: Students who can express the main idea "contains the core problem of a paragraph" are 78%, and 88% of the students can express the main idea "Has supporting sentences or explanatory sentences", expressed"The main idea is stated clearly (not complicated)" as much as 80%, expressed the main idea "There is only one main idea in a paragraph" as much as 83%.